2013
DOI: 10.1111/j.1467-6478.2013.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Second‐hand Emotion? Exploring the Contagion and Impact of Trauma and Distress in the Asylum Law Context

Abstract: Applicants' accounts of experiences of fear, trauma, violence, and persecution are central to the process of claiming asylum. These narratives are, at a human level, primed to provoke emotional responses, not only in the narrator but also in those to whom the account is relayed. In this article, we explore the vectors of emotionality that permeate asylum decision‐making in the United Kingdom, focusing particularly on the risk faced by the professionals involved of suffering vicarious trauma. More specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 10 publications
0
46
0
2
Order By: Relevance
“…Finally, Baillot, Cowan, and Munro (2013) found evidence in case managers handling claims for asylum seekers of STS adversely affecting job performance, threatening their clients' chances of obtaining asylum. Furthermore, case managers used a range of putatively maladaptive coping strategies, such as denial of responsibility and detachment, in a bid to avoid the contagion of distressing client emotions.…”
Section: Lawyers and Compassion Fatiguementioning
confidence: 99%
“…Finally, Baillot, Cowan, and Munro (2013) found evidence in case managers handling claims for asylum seekers of STS adversely affecting job performance, threatening their clients' chances of obtaining asylum. Furthermore, case managers used a range of putatively maladaptive coping strategies, such as denial of responsibility and detachment, in a bid to avoid the contagion of distressing client emotions.…”
Section: Lawyers and Compassion Fatiguementioning
confidence: 99%
“…This particularly gendered form of disbelief problematically conflates assessments of empirical likelihood with substantive veracity; it is generally accepted across the asylum field that women face rape much more frequently than men, but the fact that rape narratives are heard more often in the context of women's claims means that the mundane reality of heterosexual gender violence seems in itself to provide a reason to disbelieve the women. It also highlights the extent to which hearing repeated stories of sexual violence recounted by women can render some decision-makers case-hardened in ways that limit their capacity not only for empathy towards the applicant, but also for belief in her account (see further, Baillot et al , 2013). Indeed, in her study, Jubany (2011) found that since women applicants who indicated a history of sexual assault were more likely to be interviewed by women, the limited number of women officers were liable to hear such accounts more regularly, which may effect increased desensitisation and scepticism on the part of female decision-makers.…”
Section: ‘How Credible Can a Rape Story Be?’ Scepticism About Women'smentioning
confidence: 99%
“…Meanwhile, several UKBA personnel reflected on their experiences of political pressure from both sides of the asylum debate. As one Presenting Officer put it, for example, We have previously suggested that conducting inherently emotionally challenging labour, particularly in this sort of contested, constrained and politicised context, can increase the risk of 'burn-out' or 'case-hardening' amongst professionals and may encourage the development of coping strategies that distance decision-makers from applicants and support the adoption of an automatically sceptical perspective in relation to their claims (Baillot, Cowan and Munro 2013). Such concerns are also raised in recent work by Jubany, indicating that feelings of discontent and "apathy towards the fairness of the system" (2011: 80) amongst UK and Spanish asylum decision-makers encouraged them to form their own values and norms, which in turn informed the operational culture of the immigration service.…”
Section: General Scepticism -The 'Culture Of Disbelief'mentioning
confidence: 99%
See 1 more Smart Citation
“…This is potentially vital when trying to deconstruct the reasons why initiatives such as training and guidelines may not bring about fundamental changes in decision makers' (gendered) interpretations of refugee law (see e.g. Baillot et al, 2013).…”
mentioning
confidence: 99%